A study to assess the maternal and perinatal outcome of postdated pregnancy at a tertiary care institution of Eastern India - Saurabh, Suvidha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Post term pregnancy has been defined as a pregnancy that persists beyond 294 days or 42 weeks of gestation. It most likely occurs in less than 5% gestation and has been associated with increased perinatal mortality rate. There is a strong body of evidence that the induction of labour at term and prior to 42 weeks of gestation is associated with reduction in perinatal complications without an associated increase in CS rates. Methods: This observational study was carried out in obstetrics/gynaecology department of ESIC Medical College and Hospital, Bihta. All the primi or multi gravida beyond the expected date of delivery and coming under the inclusion criteria were taken. Taking in consideration about the incidence of cases of post term deliveries last year, we are getting 6 to 7 cases every month. So,70 cases in 1 year of study duration was taken from October 2022 to September 2023. Results: This observation study showed that the incidence of postdated pregnancy was higher in primi gravida. Incidence of fetal distress and NICU admissions increased as the period of gestation increases. Conclusions: Post dated pregnancy was associated with perinatal complications like fetal distress, meconium aspiration syndrome and fetal asphyxia. There was increased risk of obstetric complications like postpartum haemorrhage, perineal tear, cervical tear and shoulder dystocia. Management of postdated pregnancy is a challenge to obstetrician and policies regarding induction of labour beyond expected date of delivery can reduce untoward complications.